2010
DOI: 10.1007/978-1-4419-6448-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia de Lange Syndrome

Abstract: C ornelia de Lange syndrome (CdLS) (OMIM # 122470, #300590 and #610759) is an autosomal dominant disorder that is classically characterized by typical facial features, growth and mental retardation, upper limb defects, hirsutism, gastrointestinal and other visceral system involvement. Heterozygous mutations in the cohesin regulator, NIPBL, or the cohesin structural components SMC1A and SMC3, have been identified in approximately 65% of individuals with CdLS. Cohesin regulates sister chromatid cohesion during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 121 publications
(128 reference statements)
1
23
0
1
Order By: Relevance
“…Interestingly, four transcripts (DCX [58], ATRX [59], MECP2 [60] and NIPBL [61]) regulated under siRNA against (P)RR have also been associated with mental retardation and/or epilepsy (Table S12 in File S1). Moreover, the genes RELN [58] and SIM1 [62], regulated by PLZF overexpression, are involved in epilepsy and mental retardation, respectively (Table S12 in File S1).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, four transcripts (DCX [58], ATRX [59], MECP2 [60] and NIPBL [61]) regulated under siRNA against (P)RR have also been associated with mental retardation and/or epilepsy (Table S12 in File S1). Moreover, the genes RELN [58] and SIM1 [62], regulated by PLZF overexpression, are involved in epilepsy and mental retardation, respectively (Table S12 in File S1).…”
Section: Discussionmentioning
confidence: 99%
“…Pie et al (2010) found that CdLS patients with mutations in SMC1A had a higher incidence of high palate anomalies, but no mutation in SMC1A was identified in our patient 4 with cleft palate. It is possible that mutations affecting the remaining structural components of the cohesin complex (Rad21 or Stag2) or mutations in regulatory sequences for NIPBL might occur in some of the patients without detected mutations in target sequences of NIPBL, SMC1A, or SMC3 (Liu and Baynam, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Beim Cornelia-de-Lange-Syndrom handelt es sich um eine Erkrankung, die multiple Organsysteme betreffen kann. So liegen neben den Dysmorphien des Gesichtes mit Hirsutismus und Lippenanomalien auch häufig eine mentale und eine körperliche Retardierung vor [3]. Weiter bestehen gastroösophageale Dysfunktionen sowie kardiale und urogenitale Fehlbildungen [4].…”
Section: Klinische Befundeunclassified